Pengaruh Kemajuan Teknologi Dalam Hukum Investasi Di Indonesia - Mardhiyah; Tuti Sayekti; Abdurrahman Saleh; Rico Febriansyah; Wendi Sastra (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The advancement of digital technology has significantly influenced the dynamics of investment law in Indonesia. Innovations such as financial technology (fintech), cryptocurrency, and digital trading platforms have expanded access to investment opportunities while simultaneously introducing new legal risks. This study aims to examine the impact of technological progress on regulation, legal protection for investors, and law enforcement against violations, including cybercrime and investment fraud. Employing a normative juridical approach, the analysis draws on legislation, court decisions, and recent academic literature. The findings indicate that inadequate regulation, weak supervisory mechanisms, and low legal literacy among investors remain major obstacles. Therefore, adaptive legal reform is required through specific regulations on digital transactions, strengthened oversight, and enhanced collaboration among government, industry, and society. This study underscores the necessity of responsive investment law in addressing technological developments and contributes to the academic discourse on regulatory transformation in the digital era.